Basal forebrain activation improves working memory in senescent monkeys - Kendyl R. Pennington; Luca Debs; Sophia Chung; Janki Bava; Clément M. Garin; Fernando L. Vale; Sarah K. Bick; Dario J. Englot; Alvin V. Terry, Jr.; Christos Constantinidis; David T. Blake (Brain Stimulation)
Brain aging contributes to cognitive decline and risk of dementia. Degeneration of the basal forebrain cholinergic system parallels these changes in aging, Alzheimer's dementia, Parkinson's dementia, and Lewy body dementia, and thus is a common element linked to executive function across the lifespan and in disease states. Here, we tested the potential of one-hour daily intermittent basal forebrain stimulation to improve cognition in senescent Rhesus monkeys, and its mechanisms of action. Stimulation in five animals improved working memory duration in each animal over 8–12 weeks, with peak improvements observed in the first four weeks. In an ensuing three month period without stimulation, improvements were retained. With additional stimulation, performance remained above baseline throughout the 15 months of the study. Studies with a cholinesterase inhibitor in five animals produced inconsistent improvements in behavior. One of five animals improved significantly. Manipulating the stimulation pattern demonstrated selectivity for both stimulation and recovery period duration in two animals. Brain stimulation led to acute increases in cerebrospinal fluid levels of tissue plasminogen activator, which is an activating element for two brain neurotrophins, Nerve Growth Factor (NGF) and Brain-Derived Growth Factor (BDNF), in four animals. Stimulation also led to improved glucose utilization in stimulated hemispheres relative to contralateral in three animals. Glucose utilization also consistently declines with aging and some dementias. Together, these findings suggest that intermittent stimulation of the nucleus basalis of Meynert improves executive function and reverses some aspects of brain aging.